2009
DOI: 10.1002/adsc.200900087
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Recombinant Escherichia coli Catalysts which Simultaneously Express an (S)‐Oxynitrilase and Different Nitrilase Variants for the Synthesis of (S)‐Mandelic Acid and (S)‐Mandelic Amide from Benzaldehyde and Cyanide

Abstract: Recombinant Escherichia coli strains were constructed which simultaneously expressed the genes encoding the (S)-oxynitrilase from cassava (Manihot esculenta) together with the wild-type or a mutant variant of the arylacetonitrilase from Pseudomonas fluorescens EBC191 in a single organism under the control of a rhamnose-inducible promoter. The whole cell catalysts obtained converted benzaldehyde and potassium cyanide in aqueous media at pH 5.2 mainly to (S)-mandelic acid and/or (S)-mandelic amide and synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The analysis of the chemically synthesized atrolactamide by chiral HPLC (conditions described above) demonstrated the presence of two signals (retention time [R t ] of 2.3 min and R t of 3.8 min). In order to correlate these signals with the respective enantiomers, acetophenone plus cyanide were converted by E. coli JM109(pIK9)(pJOE5361.1), which simultaneously expressed the (S)-oxynitrilase from cassava (Manihot esculenta) and the nitrilase from P. fluorescens EBC191 and which had been successfully used for the production of (S)-mandelic acid and (S)-mandeloamide from benzaldehyde plus cyanide (40). Thus, it was found that during the reaction, the signal with an R t of 3.8 min was formed preferentially, which was thus identified as (S)-atrolactamide.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of the chemically synthesized atrolactamide by chiral HPLC (conditions described above) demonstrated the presence of two signals (retention time [R t ] of 2.3 min and R t of 3.8 min). In order to correlate these signals with the respective enantiomers, acetophenone plus cyanide were converted by E. coli JM109(pIK9)(pJOE5361.1), which simultaneously expressed the (S)-oxynitrilase from cassava (Manihot esculenta) and the nitrilase from P. fluorescens EBC191 and which had been successfully used for the production of (S)-mandelic acid and (S)-mandeloamide from benzaldehyde plus cyanide (40). Thus, it was found that during the reaction, the signal with an R t of 3.8 min was formed preferentially, which was thus identified as (S)-atrolactamide.…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli JM109 was used as the host strain for all plasmids. The cultivation and induction conditions for the recombinant strains used were described previously (16,20,40). Enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, (R)-(−)-mandelic acid, widely used for the production of semisynthetic cephalosporins and anti-obesity agents, is produced by hydrolyzing mandelonitrile [5,8]. In addition, other studies focused on strategic optimizations for increasing the reaction rate, reducing substrate inhibition, and improving enzyme enantioselectivity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%